2002
DOI: 10.3168/jds.s0022-0302(02)74406-8
|View full text |Cite
|
Sign up to set email alerts
|

Cholesterol Removal from Media by Lactococci

Abstract: Elevated serum cholesterol in humans is generally a risk factor correlated with the development of coronary heart disease. It has been reported that a culture of Lactobacillus acidophilus actively taking up cholesterol from a laboratory medium would function in vivo to exert a hypocholesterolemic effect. In the present study, seven strains of the genus Lactococcus were examined for their ability to remove cholesterol from laboratory media during growth. All strains of lactococci tested could remove cholesterol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
112
2
12

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 160 publications
(141 citation statements)
references
References 20 publications
15
112
2
12
Order By: Relevance
“…Apparently, cholesterol reduction varied among the tested bacterial strains ranged from 48.22 to 71.6% reduction from the initial cholesterol concentration and the highest reduction mean values of 71.6 and 68.38% were obtained by the two isolates Y1 and W7, respectively. The results in the present study are in accordance with the experimental findings of Sieladie et al (2011) who reported that about 11 lactobacilli strains isolated from raw cow milk exhibited cholesterol Kimoto et al (2002). It has been reported that cholesterol removal by lactic acid bacteria appeared not to be the only strain specific but also growth dependent, as shown by studies that have evaluated cholesterol removal by probiotic cells during different growth conditions (Kimoto et al, 2002).…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Apparently, cholesterol reduction varied among the tested bacterial strains ranged from 48.22 to 71.6% reduction from the initial cholesterol concentration and the highest reduction mean values of 71.6 and 68.38% were obtained by the two isolates Y1 and W7, respectively. The results in the present study are in accordance with the experimental findings of Sieladie et al (2011) who reported that about 11 lactobacilli strains isolated from raw cow milk exhibited cholesterol Kimoto et al (2002). It has been reported that cholesterol removal by lactic acid bacteria appeared not to be the only strain specific but also growth dependent, as shown by studies that have evaluated cholesterol removal by probiotic cells during different growth conditions (Kimoto et al, 2002).…”
Section: Resultssupporting
confidence: 93%
“…Different mechanisms for cholesterol removal by probiotics have been reported, such as deconjugation of bile salts by bile-salt hydrolase (BSH) (Ahn et al, 2003), cholesterol absorption into bacterial cell membranes (Kimoto et al, 2002), production of short-chain fatty acids (SCFAs) during the probiotics growth (Trautwein et al, 1998), and cholesterol transformation into coprostanol (Lye et al, 2010). Additionally, several cultural conditions such as media composition, pH, temperature, and inoculum size may change the metabolic pathways by altering pyruvate metabolism and external electron acceptors resulted in different end-products (Axelsson, 1998;Annuk et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…They also observed that assimilation occurred both at pH 6.0 and without pH control. Similar results have been reported for bifidobacteria [73] and lactococci [28]. Kimoto et al [28] observed that both live and heat-killed Lactococcus lactis subsp.…”
Section: Proposed Mechanisms Of Cholesterol Reduction By Lactic Acid supporting
confidence: 81%
“…Similar results have been reported for bifidobacteria [73] and lactococci [28]. Kimoto et al [28] observed that both live and heat-killed Lactococcus lactis subsp. lactis biovar diacetylactis N7 were able to remove cholesterol from growth media.…”
Section: Proposed Mechanisms Of Cholesterol Reduction By Lactic Acid supporting
confidence: 81%
See 1 more Smart Citation